Risk factors associated with prolonged hospital stay in Neonatal Intensive Care: a case-control study.: Factores de riesgo asociados a estancia hospitalaria prolongada en Cuidados Intensivos Neonatales: un estudio de casos y controles. - Victorio Arribasplata , Gladys Edith (2023)
Objective: Identify neonatal pathologies or conditions that influence the prolongation of hospital stay in a Neonatal Intensive Care Unit (NICU). Materials and methods: An observational, retrospective, case-control study was carried out; in neonates hospitalized in the NICU, during the period 2015-2019, considering their perinatal and postnatal diagnoses as factors to be evaluated, as well as hospital stay. Two groups were divided: cases (prolonged stay) and controls (non-prolonged stay). The collected data were processed in the SPSS v.23 program, obtaining the OR and the Binary Logistic Regression. Results: 361 neonates (91 cases and 270 controls) were included, finding significance in perinatal factors (p<0.05): Birth weight (1000g to <1500g, ORa 8.2: CI3.1 - 21.2) and gestational age (28 to 31 weeks , ORa 18.6: CI4.8-71.4; 32-33 weeks, ORa 8.1: CI3.5 – 18.4); and postnatal factors (p<0.05): RDS (ORa 10.3: CI 4.8-22.2), PHT (OR 32.2: CI 1.8-559.0), sepsis (ORa 7.1: CI 3.1-16.0), Neonatal malnutrition (ORa 10.2: CI 4.7 -22.1) and anemia of prematurity (aOR 8.3: CI 2.4-28.1). The following did not reach significance: asphyxia, transient tachypnea of ​​the newborn, pneumonia, pneumothorax, bronchopulmonary dysplasia, meconium aspiration syndrome, patent ductus arteriosus, congenital heart disease, hyperbilirubinemia, hypoglycemia, necrotizing enterocolitis, and apnea of ​​prematurity. Conclusions: Birth weight, gestational age, RDS, PHPT, sepsis, neonatal malnutrition and anemia of prematurity are risk factors for prolonged hospital stay.